2020
DOI: 10.1097/acm.0000000000003064
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Validity of the New MCAT Exam

Abstract: Purpose To conduct a study of the validity of the new Medical College Admission Test (MCAT). Method Deidentified data for first- and second-year medical students (185 women, 54.3%; 156 men, 45.7%) who matriculated in 2016 and 2017 to the University of Minnesota Medical School–Twin Cities were included. Of those students, 220 (64.5%) had taken the new MCAT exam and 182 (53.4%) had taken the old MCAT exam (61 [17.9%] had taken both). The authors calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Both in and outside of the medical career space, performance on one standardised exam is seen as a predictor of performance on the next, and thus an applicant's MCAT performance is judged as a predictor of USMLE success. Both the previous and ongoing MCAT validity studies have suggested that the combined GPA and MCAT credentials are more predictive than either factor alone 22,23 . Preliminary data in the 2015 MCAT Validity Study support the notion that 2015 MCAT scores correlate with medical student advancement and Step I performance, however, an internal review at our institution did not corroborate this with statistical significance, and only a weak correlation was observed.…”
Section: Discussionmentioning
confidence: 62%
“…Both in and outside of the medical career space, performance on one standardised exam is seen as a predictor of performance on the next, and thus an applicant's MCAT performance is judged as a predictor of USMLE success. Both the previous and ongoing MCAT validity studies have suggested that the combined GPA and MCAT credentials are more predictive than either factor alone 22,23 . Preliminary data in the 2015 MCAT Validity Study support the notion that 2015 MCAT scores correlate with medical student advancement and Step I performance, however, an internal review at our institution did not corroborate this with statistical significance, and only a weak correlation was observed.…”
Section: Discussionmentioning
confidence: 62%
“…Our results are in the expected pattern of magnitude that previous studies have demonstrated (Ferguson et al, 2002 ; Gauer et al, 2016 ; Kulatunga-Moruzi & Norman, 2002 ; Song et al, 2011 ). For example, in a recent study, the four new MCAT exam section scores explained 19% of the variance on USMLE Step 1 performance (Violato et al, 2020 ). Adding the PBPM program GPA explained an additional 10% and 7% for preclerkship and USMLE Step 1 performance, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The entire questionnaire survey process was conducted with the consent of the participants; the questionnaire was not open to the public and only for research purposes. In order to test the reliability of the questionnaire, the Cronbach's α coefficient is adopted for evaluation [31], and the validity of the questionnaire is analyzed by principal component analysis (PCA) [32].…”
Section: Research Design and Model Constructionmentioning
confidence: 99%